A rare case of folliculotropic mycosis fungoides with eosinophilic pneumonia. Issue 4 (8th February 2022) - Hanaoka, Yuma; Kiyohara, Eiji; Tani, Mamori; Kusakabe, Shinsuke; Maeda, Tetsuo; Tanemura, Atsushi; Fujimoto, Manabu
Abstract : We describe the first case of folliculotropic mycosis fungoides (FMF) involving eosinophilic pneumonia (EP). It would be difficult to treat EP without CTCL treatment.